Weight change across adulthood in relation to the risk of depression - Wang, Tao; Dai, Bingqin; Shi, Huanchen; Li, Huawei; Fan, Kexin; Zhang, Dongfeng; Zhou, Yunping (Frontiers in Psychology, 2023)
Background: Studies examining weight change patterns and depression are scarce and report inconsistent findings. This study -aimed to elucidate the association between weight change patterns and the risk of depression in a large, representative sample of US adults.Methods: Data from the National Health and Nutrition Examination Survey (NHANES) 2005-2018 was analyzed. Five weight change groups were categorized: stable normal, weight loss, weight gain, maximum overweight, and stable obesity. Depression was ascertained using the validated Patient Health Questionnaire (PHQ-9) and depression was defined as PHQ score ≥10.2 This is a provisional file, not the final typeset article Conclusions: Our study suggested that stable obesity and weight gain across adulthood were associated with increased risks of depression.